Nail changes secondary to hand-foot-mouth disease - Akpolat, Nebahat Demet; Karaca, Nezih (The Turkish Journal of Pediatrics, 2016)
Hand-foot-mouth disease (HFMD) is a viral disease that is characterized by palmoplantar vesicular eruption and erosive stomatitis. Beau’s line and onychomadesis can be observed as late findings following HFMD due to arrest in nail matrix. We aimed to draw attention to HMFD and nail changes, which have been seen more frequently. Demographic characteristics and nail findings of 15 children, who were diagnosed with HFMD in the dermatology clinic of Beykoz State Hospital between August 2015-October 2015 were evaluated. Mean age of the patients was 5.13 years (1-13 years), 66.6% were boys (n=10), and 33.4% were girls (n=5); 53.3% were diagnosed in August (n=8). Dermatologic examinations revealed palmar and plantar vesicular eruptions in all cases, additionally one patient had vesicular eruptions also on hip, legs, and arms. Erosive stomatitis was present in oral mucosa of 60% of patients (n=9). Nail findings were determined after a mean of 4.06 weeks following HFMD. Onychomadesis and Beau’s line were present in 66.6% (n=10) and 33.4% of the patients, respectively. Hand-foot-mouth disease is a viral infection of childhood, which may be seen as isolated cases or epidemics, and characterized with palmoplantar vesicular eruption and erosive stomatitis. Being aware that Beau’s line and onychomadesis can be seen as late findings of HFMD and should relieve without treatment, will prevent unnecessary diagnostic and invasive interventions.